DIGITAL RESILIENCE, CYBERSECURITY AND SUPPLY CHAINS - Singh, Tarnveer (ROUTLEDGE, 2025)
In the digital era, the pace of technological advancement is unprecedented, and the interconnectivity of systems and processes has reached unprecedented levels. While this interconnectivity has brought about numerous benefits, it has also introduced new risks and vulnerabilities that can potentially disrupt operations, compromise data integrity, and threaten business continuity. In today's rapidly evolving digital landscape, organisations must prioritise resilience to thrive. Digital resilience encompasses the ability to adapt, recover, and maintain operations in the face of cyber threats, operational disruptions, and supply chain challenges. As we navigate the complexities of the digital age, cultivating resilience is paramount to safeguarding our digital assets, ensuring business continuity, and fostering long-term success. Digital Resilience, Cybersecurity and Supply Chains considers the intricacies of digital resilience, its various facets, including cyber resilience, operational resilience, and supply chain resilience. Executives and business students need to understand the key challenges organisations face in building resilience and provide actionable strategies, tools, and technologies to enhance our digital resilience capabilities. This book examines real-world case studies of organisations that have successfully navigated the complexities of the digital age, providing inspiration for readers' own resilience journeys.
Keywords: Computer security.; elektronické knihy; electronic books